Penentuan Harga Jual Paket Edukasi Wisata dengan Pendekatan Biaya Pada Padhepokan Panji Asmoro Bangun - Fajar Rina Sejati; Dian Pertiwi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This activity was carried out at Padhepokan Panji Asmoro Bangun, an art center with panji masks as a typical culture of Malang Regency, East Java, Indonesia. This assistance is carried out by the Abdimas Team under the ADAI organization, via hybrid (offline and online). The purpose of this assistance is to provide assistance on how to calculate the selling price of tour packages using a cost approach. The mentoring methods used are lecture methods and training in the form of demonstrations. The results of the assistance show that there has been no determination of an appropriate and affordable selling price for the community. The selling price used so far is only an estimate and does not use calculations of the related cost elements. The advice is to pay attention to 5 (five) stages in determining the selling price of tour packages, including market research, identifying cost elements, calculating operational costs, determining profit margins, and calculating the selling price of tour packages.